Age Estimation Using The Willems Method With Panoramic Radiography In Patients At RSGM YARSI - okky marita; Rayyen Alfrian Juneanro; Moch Atmaji Windrianto (YARSI Dental Scientific Meeting - e Journal, 2025)
Introduction: Teeth meet the requirements for being used as a means of identification due to their high individuality factor. Age estimation significantly contributes to the identification of forensic teeth in specimen investigations. Objective: This study aims to determine age estimation using the Willems method with panoramic radiography in patients at the RSGM YARSI, and the Islamic perspective on this matter. Material and Methods: This research is an observational analytic study with a cross-sectional design. Samples were taken using purposive sampling method, totaling 70 patients aged 4-15 years who were in the developmental stage of seven teeth and underwent panoramic radiography at RSGM YARSI. Data collection of panoramic radiography results followed by age estimation calculation by assessing the developmental stages of the seven lower jaw teeth using the Willems method. The analysis techniques used were univariate and bivariate analysis. Result: The results showed that in males the p value = 0.223 (p>0.05), in females the p value = 0.0001 (p<0.05). The Wilcoxon test results showed that there was a significant difference with the p value = 0.001 (p<0.05) in all male and female samples. Conclusion: There was no significant difference between dental age and chronological age in male samples, but there was a significant difference in female samples. In the entire sample, there was a significant difference between dental age and chronological age.